"We ARE our instrument!": Forming a singer identity. (June 2015) - O'Bryan, Jessica
Preparation for the operatic stage means that for some students their voice will undergo significant transformation during training. For most operatic singers, voice type will determine future roles, the music they perform and potential career trajectory. Voice type becomes a facet of identity and position within the operatic world. This article presents a narrative thematic analysis of a young woman's account of her teaching and learning experiences in preparation for a career on the operatic stage. Two semi-structured interviews were conducted, and beliefs and values about her singing and voice type were elicited. This article discusses how significant changes to her voice have affected her self-concept, singer identity and potential career in opera. Also discussed is the impact of conservatorium environment, peers and mentors on her feelings of self-belief.